Epidemiological Profile of Measles Cases in Azad Jammu & Kashmir, Pakistan: 2018 - Hafeez, Uzma (International Journal of Pathology, 2021)
Background: Measles is a highly contagious viral disease with significant childhood morbidity and mortality. This study was carried out to assess the magnitude of measles cases and its description with respect to socio demographic and clinical characteristics during 2018 in AJ& K. Methodology: This descriptive study was carried out on secondary data received at the Directorate General Health Muzaffarabad. A suspected measles case was defined as “ any child of age < 15 years, belonging to either sex and resident of the state of Azad Jammu & Kashmir with non-vesicular macula papular rash and fever along with one of the symptoms of cough, coryza and conjunctivitis from 1st January 2018 to 31st December 2018.A confirmed case of measles was defined as “a suspected case of measles who is laboratory confirmed by the presence of measles-specific IgM antibodies.”.Line listing of all cases was done and data was analyzed by person place and time and frequencies proportions and rates were calculated. Results: A total of 561 cases were recorded in which 58% (n=305) were males. The median age of cases was 30 months (range 2-180 months). Majority of cases (80%) were below 6 years of age. The Epi-curve showed that peak cases were reported from 20th epidemiological week to 27th week and thereafter the cases showed gradual decline. Fever and rash were associated with cough (87%) runny nose (75%) and conjunctivitis (63%). Majority of cases were reported from tertiary care hospitals followed by secondary care health facilities. Conclusion: Most of the children with measles were up to 3 years of age group and were either not immunized or partial immunized against measles. Continuation of VPD surveillance and strengthening of routine immunization is the solution to achieve and sustain 100% immunization coverage rate in Azad Jammu & Kashmir